Bacteriocins: An Overview of Antimicrobial, Toxicity, and Biosafety Assessment by in vivo Models - Benítez-Chao, Diego Francisco; León-Buitimea, Angel; Lerma-Escalera, Jordy Alexis; Morones-Ramírez, José Rubén (Frontiers in Microbiology, 2021)
The world is facing a significant increase in infections caused by drug-resistant infectious agents. In response, various strategies have been recently explored to treat them, including the development of bacteriocins. Bacteriocins, are a group of antimicrobial peptides, produced by bacteria, capable of controlling clinically relevant susceptible and drug resistant bacteria. Bacteriocins have been studied to be able to modify and improve their physicochemical properties, pharmacological effects, and biosafety. This manuscript focuses on the research being developed on the biosafety of bacteriocins, which is a topic that has not been addressed extensively in previous reviews. This work discusses the studies that have tested the effect of bacteriocins against pathogens and assess their toxicity using in vivo models, including murine and other alternative animal models. Thus, this work concludes the urgency to increase and advance the in vivo models that both assess the efficacy of bacteriocins as antimicrobial agents, but also evaluate possible toxicity and side effects, which are key factors to determine their success as potential therapeutic agents in the fight against infections caused by multi-drug resistant microorganisms.